Analysis of Vegetation Along the Highway (Ramadi -Ar Rutba) in the Western Desert of Iraq - al-Alwani, AbdulKarim; Mousa, Mohammed; Al-Fahdawi, Lattief (Iraqi Journal of Science, 2024)
This study was conducted along the desert road to traffic speed (Ramadi -Ar Rutba) to cross the Western Desert of Iraq during the period from early April 2010-1122, with the height of the topography of the region ranges between 56 and 617 meters above sea level, covering a distance of about 310 km from the city of Ramadi in central Iraq to the south-west towards the Ar Rutba City.The main objective was to study the analysis of vegetation spread on both sides of Highway and knowledge of environmental characteristics within this geographical area and to identify the values of plant community characteristics as indicators of interest include: diagnosis of plant species, density, frequency, abundance and biomass of coverage. The study was based on the analysis of the vegetation in 42 square randomly and have been identified a total of 92 species of plants, belonging to 27 plant families are: Compositae, Aizoaceae, Boraginaceae, Leguminosae, Chenopodiaceae, Malvaceae, Euphorbiaceaa, Cucurbitaceae, Zygophyllaceae, Crucifereae, Labiateae, Resedaceae, Caryophyllaceae, Frankeniaceae, Ephedraceae, Convolvulaceae, Cistaceae, Cappariaceae, Rutaceae, Ranunculaceae, Polygonaceae, Plantaginaceae, Orobanchiaceae, Geraniaceae, Liliaceae, Gramineae, Amaranthaceae, There sovereignty for families Chenopodiaceae, Crucifereae, Leguminosae and the Compositae, one of the species under trees, while prevail families from other types of herbal perennial and annuals, has been observed that the climate and topographic recipes soils and overgrazing are influential factors in the formation and distribution of these plant communities.